Priority directions of Ukrainian-Chinese cooperation in industry (Economics and region, 2022)
The article argues the priority areas of Ukrainian-Chinese cooperation in the industrial sphere. It has been established that a large number of documents on further cooperation have been developed between Ukraine and China, but the effectiveness of their implementation is extremely low. The main priorities in the development of Chinese and Ukrainian industry have been identified. It is established that the main priorities for the development of Chinese industry include: development of new information technologies; production of numerical control tools and robotics; production of space and aviation products; production of marine equipment and construction of high-tech ships; production of advanced railway transport equipment; production of energy-saving and transport vehicles using alternative energy sources; production of environmentally friendly energy equipment; production of agricultural machinery; development of new materials; development of biological medicine and high-tech medical devices. It is determined that among the priority areas of Ukrainian-Chinese cooperation in the industrial sphere may be: agro-industrial complex; machine-building complex; transport infrastructure; processing industry, etc. It is shown that the main interest of Chinese investors is in the field of complex implementation of infrastructure projects (construction sphere) and agriculture. Mechanisms for attracting Chinese investments in priority areas of Ukrainian industry are considered. It is established that China provides credits, usually for the purchase of equipment made in China, thus providing support to its industrial sector and significant volume of export goods. It is shown that Ukrainian-Chinese cooperation in the industrial sphere has both advantages from the inflow of investments and threats from a possible targeted change in investments by investors.
Keywords: Ukrainian-Chinese cooperation; industry; investments; joint projects